(untitled) (Journal of Global Accounting, 2023)
The study examines the effect of fraud pressure elements of fraud pentagon on fraud prevalence in Deposit Money Banks (DMBs) in Nigeria. The study adopted the ex post facto research design. This is because the Independent variables were studied in retrospect for seeking possible and plausible relations. The population comprised of quoted Deposit Money Banks. The final sample delimited to thirteen (13) Deposit Money Banks listed on the Nigerian Exchange Group (NGX) as at end of 2021. The data utilised in the study were drawn from the annual report and accounts of the Deposit Money Banks for the years 2012-2021. The data were analyzed using descriptive and inferential statistical analyses. The hypotheses were tested using the multiple linear regression technique. The study finds that there is a significant (negative) effect of pressure on fraudulent financial reporting in deposit money banks (p<.05). Based on this, the study recommends that auditors should look out for the pressure risk in examining financial transactions in order to control fraudulent financial reporting in Deposit Money Banks. Managers and shareholders strengthen corporate governance practices in the DMBs.